KEJADIAN PTERIGIUM PADA PENDUDUK YANG TINGGAL DISEKITAR PANTAI DI KECAMATAN BAGAN DELI KECAMATAN MEDAN BELAWAN - DEWI MEILINDATARI NASUTION (LP2MTBM MAKARIOZ, 2023)
In carrying out their lives, the people of the Bagan Deli area are faced with problems with climatic conditions around the beach that are dry and dusty, causing wind with dry air and having dust carried by Sea Sand, plus strong sunlight, and disturbing dust particles that can cause damage to the growth of eye tissue. This study used analytical descriptive method with cross sectional approach, The results of the study concluded from several risk factors that exist and are susceptible to Pterygium disease, where the risks that exist, so that it has a significant relationship with Pterygium are risk factors for age, sex and occupation, where the largest number of people affected by Pterygium is the number of female population, the number of residents in the age range of 40-49 years and residents who work as fishermen.